Emerging MR Imaging and Spectroscopic Methods to Study Brain Tumor Metabolism - Kumar, Manoj; Nanga, Ravi Prakash Reddy; Verma, Gaurav; Wilson, Neil; Brisset, Jean Christophe; Nath, Kavindra; Chawla, Sanjeev (Frontiers in Neurology, 2022)
Proton magnetic resonance spectroscopy (1H-MRS) provides a non-invasive biochemical profile of brain tumors. However, the conventional 1H-MRS methods present a few challenges mainly related to limited spatial coverage and low spatial & spectral resolutions. In the recent past, the advent and development of more sophisticated metabolic imaging and spectroscopic sequences have revolutionized the field of neuro-oncologic metabolomics. In this review article, we will briefly describe the scientific premises of three-dimensional echoplanar spectroscopic imaging (3D-EPSI), two-dimensional correlation spectroscopy (2D-COSY), and chemical exchange saturation technique (CEST) MR imaging techniques. Several published studies have shown how these emerging techniques can significantly impact the management of glioma patients by determining glioma grades, molecular profiles, and planning treatment, and assessing therapeutic response. The purpose of this review article is to summarize the potential clinical applications of these techniques in studying brain tumor metabolism.